2017
DOI: 10.1007/s10508-017-1068-4
|View full text |Cite
|
Sign up to set email alerts
|

Sadistic Offender or Sexual Sadism? Taxometric Evidence for a Dimensional Structure of Sexual Sadism

Abstract: Severe sexual sadism is a disorder of sexual preferences that focuses on humiliation and domination of the victim, sometimes causing grievous injury or death. Because offenders with high levels of sadism represent a risk to both reoffend and cause considerable harm should they reoffend, a diagnosis of sexual sadism has serious implications. The actual diagnosis of sexual sadism is fraught with problems (i.e., low reliability and validity) and exhibits poor consistency across assessments and studies (Levenson, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…The aim of the present study was to investigate the latent structure of psychopathy in a Chinese prisoner sample, measured by the YPI-SV. As found in other latent structure analyses focused on personality (Longley et al, 2017;Longpré, Guay, Knight, & Benbouriche, 2018;Tran et al, 2018), the latent structure was found to be dimensional in the present study, which was further confirmed using factor analysis methods. More and more studies show that psychopathy is a bifactor model, which defines both a general factor and several specific factors (Boduszek, Dhingra, Hyland, & Debowska, 2016;Debowska, Boduszek, Kola, & Hyland, 2014;Patrick, Hicks, Nichol, & Krueger, 2007;Zwaanswijk, Veen, & Vedder, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The aim of the present study was to investigate the latent structure of psychopathy in a Chinese prisoner sample, measured by the YPI-SV. As found in other latent structure analyses focused on personality (Longley et al, 2017;Longpré, Guay, Knight, & Benbouriche, 2018;Tran et al, 2018), the latent structure was found to be dimensional in the present study, which was further confirmed using factor analysis methods. More and more studies show that psychopathy is a bifactor model, which defines both a general factor and several specific factors (Boduszek, Dhingra, Hyland, & Debowska, 2016;Debowska, Boduszek, Kola, & Hyland, 2014;Patrick, Hicks, Nichol, & Krueger, 2007;Zwaanswijk, Veen, & Vedder, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Sadism has, however, been plagued with an absence of pathognomonic symptoms, and many symptoms supposedly identifying sadism have been found among non-sadistic offenders and non-delinquents (for more details, see Longpré et al, 2018). Based on the results obtained in Longpré et al (2018), but also on the convergence of results across studies and samples, we concluded that sexual sadism is distributed as a dimension. These results are not only in stark contrast to the categorical orientation that has been and continues to be supported in the Diagnostic and Statistical Manual (e.g., American Psychiatric Association, 2013), but they also provide empirical evidence for the importance of reformulating existing categorical diagnoses of sadism.…”
mentioning
confidence: 73%
“…No potential trimodal structures were evident, either on the full scale or on the sub-scales, with a baserate of 10% and 15%, for MAMBAC, MAXEIG, and L-Mode curves (all curves available upon request). In all the taxometric studies of sexual sadism (Knight et al, 2013;Longpré, Knight, & Guay, 2019b;Longpré et al, 2019c;Mokros, Schilling, Weiss, Nitschke, & Eher, 2014), only Longpré et al (2018) produced an L-Mode that could potentially be interpreted as trimodal.…”
Section: Inadequate Consideration Of Converging Evidence For the Dimementioning
confidence: 99%
See 2 more Smart Citations